Social influence and eco-label factors towards purchaseintention of home products: A PLS approach / Nor Hashima Hashim ... [et al.] - Hashim, Nor Hashima; Yahya, Wan Kalthom; Abu Bakar, Saridan; Asrul, Siti Aisyah (Universiti Teknologi MARA Selangor, 2018)
Consumers today are more aware of environmental issues. This rise in ecologically conscious consumer behavior sometimes known as green consumers has seen an incease in many studies on the nature of green consumers in different markets. This study examines the attitude-behavior relationship that integrates two factors, namely: social influence and knowledge of eco-labels to examine their influence in the intention to purchase green home electronic products.The green home electronic products for this study are air conditioner, television and refrigerator. Using convenience sampling, 251 self-administered questionnaires were acquired from the consumers. The result indicates that social influence and eco label are significant influencers on green purchase intention of home electronic products. The results of this study will support marketers to have an all-inclusive marketing plan and promotional approaches to attract consumers to participate in buying green product. Implication for marketers is further discussed.